Study of Latest Election reforms as Electoral Bond, its Significance and Denominations - Ahmed, Ishtiyaque (Innovative Research Thoughts, 2018)
Electoral Bond is a financial instrument for making donations to political parties. These are issued by Scheduled Commercial banks upon authorisation from the Central Government to intending donors, but only against cheque and digital payments (it cannot be purchased by paying cash). These bonds shall be redeemable in the designated account of a registered political party within the prescribed time limit from issuance of bond.Electoral Bond is an effort made to cleanse the system of political funding in India. The scheme of electoral bonds addresses the concerns of donors to remain anonymous to the general public or to rival political parties.